Understanding, preventing & overcoming : osteoporosis. - Plant,Jane A.; Tidey, Gill. (Virgin London, 2003)
Osteoporosis affects approximately three million people in the UK, but the orthodox medical view is that there is no single cause. This guide suggests new scientific evidence proves that the Western diet and lifestyle are to blame - and that it is possible to reduce the risk of developing the disease.
Keywords: Osteoporosis Diet therapy